2020
DOI: 10.1149/1945-7111/ab84fc
|View full text |Cite
|
Sign up to set email alerts
|

Towards the Commercialization of the All-Solid-State Li-ion Battery: Local Bonding Structure and the Reversibility of Sheet-Style Si-PAN Anodes

Abstract: A slurry-coated sheet-style Si-based anode is developed for use in all-solid-state Li-ion batteries. Inexpensive, mixed-conducting polyacrylonitrile (PAN) is utilized as both binder and conductive additive, enabling Si-rich electrodes (70 wt%) to attain large reversible capacities ∼1,500 mAh g−1 (Si) at 1 C rates (>3 mA cm−2). Cross sectional analysis of a discharged all-solid-state half-cell indicates that the Si-PAN anode achieves the largest volumetric specific capacity ever reported for a Li-ion electrode … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 58 publications
0
29
0
Order By: Relevance
“…The nitrile group's strong polarity helps improve the electrode's electronic and ionic conductivities, so the polyacrylonitrile (PAN) can act as both adhesive and conductive additive. 73,74 In addition, the binder-free sheet-type silicon anode manufactured by removing the volatile binder signicantly improves the charge and discharge capacity of the electrode, and the reversible specic capacity is 2300 mA h g À1 aer 100 cycles. Aer 375 long-term cycles, the specic capacity exceeds 1700 mA h g À1 , showing excellent cycle stability.…”
Section: Nanostructured Silicon Anodesmentioning
confidence: 99%
See 1 more Smart Citation
“…The nitrile group's strong polarity helps improve the electrode's electronic and ionic conductivities, so the polyacrylonitrile (PAN) can act as both adhesive and conductive additive. 73,74 In addition, the binder-free sheet-type silicon anode manufactured by removing the volatile binder signicantly improves the charge and discharge capacity of the electrode, and the reversible specic capacity is 2300 mA h g À1 aer 100 cycles. Aer 375 long-term cycles, the specic capacity exceeds 1700 mA h g À1 , showing excellent cycle stability.…”
Section: Nanostructured Silicon Anodesmentioning
confidence: 99%
“…This excellent performance is also reflected in the Si anode. 74 In addition, by adjusting the distribution and nucleation sites of Sn in the Sn/SSE composite anode, the specific gravity of active materials in the composite electrode was significantly increased, showing extremely high charge–discharge capacity and capacity retention rate. 84 Nam et al demonstrated a novel Sn–C nanofiber electrode.…”
Section: Sn-based Anodesmentioning
confidence: 99%
“…Silicon (Si) or silicon (SiO 2 ) is a popular electrode material for LIBs due to its high theoretical capacity of 3579 mAh g −1[ 137 , 138 , 139 , 140 ] or 4200 mAh g −1 . [ 141 ] Further, safety performance and suitable operating potential make it promising candidate for practical batter application.…”
Section: Sulfurized Polyacrylonitrile Compositesmentioning
confidence: 99%
“…Furthermore, the pPAN/SeS 2 prepared by applying a high voltage (17 kV) exhibited a discharge capacity of 871 mAh g −1 at 4 A g −1 , which remained at 633 mAh g −1 after 2000 cycles maintaining a very low capacity decay rate (0.014% per cycle) (Figure 13g). [136] Silicon (Si) or silicon (SiO 2 ) is a popular electrode material for LIBs due to its high theoretical capacity of 3579 mAh g −1 [137][138][139][140] or 4200 mAh g −1 . [141] Further, safety performance and suitable operating potential make it promising candidate for practical batter application.…”
Section: Metal Oxides or Sulfide/sulfurized Polyacrylonitrile Compositesmentioning
confidence: 99%
“…Unfortunately, persistent dendrite formation on metallic Li over cycles remains unresolved yet, which will lead to the gradual electrode degradation and final short circuiting, hampering the large-scale implementation of ASSBs . Moreover, due to the diffusion limitation in the Li metal electrode, ASSBs usually need to be operated at current densities lower than 1.0 mA cm –2 to avoid rapid dendrite-induced failure, which fails to meet the requirements for practical applications. , Hence, It is imperative to develop alternative anode materials for next-generation high-energy ASSBs.…”
Section: Introductionmentioning
confidence: 99%